PERENCANAAN PRODUKSI DAN MATERIAL PRODUK KLEM, BRAKE DAN PLAT DI PT âXYZâ - Ayu, Ketut Gita; Septivani, Nike; Halim, Meita; Chandra, Arif; Setiawan, Florence Nathania (Industrial and Systems Engineering Assessment Journal (INASEA), 2013)
PT âXYZâis a manufacturing company specializing in pressed metal parts, dies, jigs and fixtures whichÂ is equipped with high-tech equipment and qualified human resources. PT âXYZâused a system of safety stockÂ (buffer stock) of three kanban to anticipate a shortage of stock or production of raw materials in the productionÂ process. A research was done at PT âXYZâwhich focused on the degree of conformity between actualÂ production planning by the state was obtained on the basis of the measurement of the product cycle, productionÂ capacity, actual production, production planning and material needs. The plan scheduling and materialÂ requirement planning used lot for lot method. It is needed to set the production scheduling with consideration ofÂ actual production plan where the production capacity of each product to be examined, namely the process ofbending klem = 680 pcs/hour, brake with bending process II = 680 pcs/hour and plat with a capacity of blankÂ process = 1.888 pcs/hour which are used the maximum production capacity. Lead time and safety stock are alsoÂ considered as factors affecting the scheduling. From the result of making MRP, we found that the materialÂ ordering must consider the capacity of a coil for each item and the on hand (inventory) from the last production.Â The production planning proposal of this research was able to fulfil the supply as many as three kanban. InÂ addition, the planning could increase the work productivity as well as time and cost efficiency. The MRP with lotfor lot method was declared valid because it fulfilled the assumptions of MRP for some products. PT âXYZâisÂ expected to plan a system of procurement of raw materials and production systems in order to meet marketÂ demand with the number of raw material orde. The company was expected to pay attention to lead time toÂ reduce the risk of material shortages for production.